1933
DOI: 10.1039/jr9330000395
|View full text |Cite
|
Sign up to set email alerts
|

106. The isolation of a cancer-producing hydrocarbon from coal tar. Parts I, II, and III

Abstract: Part I . Concentration of the Active Substance. By I. HIEGER. THE first experimental production of cancer by the products of distillation of coal was achieved in 1915 by Yamagiwa and Ichikawa (Mitteil. med. Facultit, kaiser. Univ. Tokyo, 1915, 15, 295), and the first enquiry into the chemical basis of tar cancer was that of Bloch and Dreifuss (Schweiz. med. Woch., 1921, 2, 1033), who concluded from their observations that the substance responsible must be a high-boiling, neutral, non-nitrogenous compound whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(97 citation statements)
references
References 0 publications
1
95
0
1
Order By: Relevance
“…Investigators therefore turned to the repeated application of cigarette smoke and its individual components to the skin of mice, the method developed for systematic studies of carcinogens in coal tar which was associated with occupational skin cancer in man. Repeated painting of mouse skin became the method of choice for demonstrating carcinogenic activity after the Kennaway group in England had used it to show that benzo(a)pyrene (BP) was the major carcinogen of coal tar (Cook et al, 1933). The isolation of BP was preceded and followed by the chemical synthesis of other carcinogenic PAHs (Cook et al, 1937;Kennaway and Hieger, 1930), some of which were later identified as minor components of coal tar.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators therefore turned to the repeated application of cigarette smoke and its individual components to the skin of mice, the method developed for systematic studies of carcinogens in coal tar which was associated with occupational skin cancer in man. Repeated painting of mouse skin became the method of choice for demonstrating carcinogenic activity after the Kennaway group in England had used it to show that benzo(a)pyrene (BP) was the major carcinogen of coal tar (Cook et al, 1933). The isolation of BP was preceded and followed by the chemical synthesis of other carcinogenic PAHs (Cook et al, 1937;Kennaway and Hieger, 1930), some of which were later identified as minor components of coal tar.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are an omnipresent class of environmental carcinogens that are byproducts of the incomplete combustion of organic matter, and thus, are produced during volcanic eruptions, and are present in automobile, jet, and factory emissions, barbequed meats and fish, and cigarette smoke (32)(33)(34)(35)(36). Benzo[a]pyrene (BP) 1 is a commonly studied PAH that has been implicated as a causative agent in lung cancer (37,38); it is metabolically activated to a number of reactive intermediates in mammals (39), including the tumorigenic (ϩ)-anti-benzo[a]pyrene diol epoxide (BPDE) (40).…”
mentioning
confidence: 99%
“…Coube a Percivall Pott, em 1775, estabelecer o nexo causal entre a atividade de limpeza de chaminés, exercida por meninos adolescentes, e o aparecimento, após muitos anos, do câncer de escroto 107 . Passados mais de 150 anos, Cook e col. 13 identificaram o benzo(alfa)pireno como o poderoso carcinóge-no responsável pelos tumores descritos, e aliás, por outros tantos, de localização diversa. Essas observações, reforçadas pelos clássicos estudos sobre câncer de bexiga em trabalhadores que manipulavam anilinas 9 , desencadearam estudos no mundo inteiro, que progressivamente resultaram em achados cada vez mais numerosos, sobre riscos oeupacionais associados à produção de neoplasias malignas.…”
Section: Câncerunclassified